A Novel and High-Effective Biosynthesis Pathway of Hesperetin-7-O-Glucoside Based on the Construction of Immobilized Rhamnosidase Reaction Platform - Wan, Wenjing; Xia, Na; Zhu, Siming; Liu, Qiang; Gao, Youcheng (Frontiers in Bioengineering and Biotechnology, 2020)
Hesperetin-7-O-glucoside (HMG) is a precursor for synthesizing a sweetener named neohesperidin dihydrochalcone, and the coordination toward flavonoids of metal ions tends to increase the water solubility of flavonoids. In order to achieve effective synthesis of HMG, an immobilized enzyme catalysis platform was constructed using an immobilized rhamnosidase on Fe3O4@graphene oxide (Fe3O4@GO), a novel reaction pathway based on the platform was designed for preparing a hesperidin complex as a soluble substrate, and ammonium hydroxide as a ligand dissociation agent to obtain HMG. The Fe3O4@GO was characterized by Fourier transform infrared (FT-IR), X-ray diffraction (XRD), scanning electron microscope (SEM) and thermal methods (TG/DSC) analysis to evaluate the immobilization matrix properties. The enzyme activity in free and immobilized form at different pH and temperature was optimized. The reusability of immobilized enzyme was also determined. In addition, the kinetic parameters (Km and Vmax) were computed after experiment. Results indicated that rhamnosidase immobilized on Fe3O4@GO using a green cross-linker of genipin hydrolyzed successfully and selectively the soluble hesperidin-Cu (Ⅱ) complex into HMG-Cu (Ⅱ), a permanent magnet helped the separation of immobilized enzyme and hydrolytes, and ammonium hydroxide was an effective ligand dissociation agent of translating HMG-Cu (II) into HMG with high purity determined by ultraviolet-visible (UV-Vis) spectra analysis and time-of-flight mass spectrometry (TOF-MS). As a result, a novel and high-effective biosynthesis pathway of HMG based on a selectively catalytic reaction platform were constructed successfully. The pathway based on the platform has great potential to produce valuable citrus monoglycoside flavonoid HMG, and the designed reaction route are feasible using the hesperidin-Cu (II) complex with good solubility as a reaction substrate and using ammonium water as a dissociation agent.